Incorporating fluoropolymer-coated micron-sized aluminum with enhanced reactivity into aluminized explosives to improve their detonation performance - Ya Guo; Kai-yuan Tan; Hui-hui Liu; Chi Hu (Energetic Materials Frontiers, 2023)
Micro-sized aluminum (m-Al) has been widely applied in explosives as fuel additives. Unfortunately, m-Al displays long ignition delay and insufficient combustion, making it fail to fully release its energy in aluminized explosives. In this work, fluoropolymer-coated m-Al composites were prepared using the solvent evaporation method. Then, the surface state of the m-Al composites was determined based on scanning electron microscopy (SEM) images, and their thermal behavior was investigated through thermogravimetric analysis (TGA) at a temperature range of 30–1200 ​°C. Moreover, the reactivity and combustion kinetics of aluminum were explored using laser ignition experiments. To evaluate the metal acceleration ability and detonation performance of CL-20-based explosives containing fluoropolymer-coated m-Al composites, the disc acceleration experiment (DAX) was specially designed taking into account the influence of aluminum particle size. The results of this study show that fluoropolymers were uniformly distributed on the surface of m-Al, and most of the as-prepared particles were microspheres without apparent agglomeration. The presence of fluoropolymers is beneficial to the oxidation of aluminum particles. The explosive sample containing fluoropolymer-coated aluminum composites exhibited shortened ignition delay and an increase in the burning speed from 3.3 ​mm·s−1 to 7.9 ​mm·s−1 compared to the sample with uncoated Al. Most especially, its specific kinetic energy increased from 8.45 ​kJ·g−1 to 9.29 ​kJ·g−1, its detonation velocity increased from 7.75 ​km·s−1 to 7.82 ​km·s−1, and its detonation pressure increased from 25.57 ​GPa to 30.89 ​GPa.